Screening for mental health and its correlates in criminal justice settings: is the inclusion of general personality and antisocial traits leading to biased estimation? - Payne, Jason (Journal of crime and justice, 2023)
Replication in the social sciences is a necessary but oft-forgotten reality. In the Australian context, cross-cultural replication is an uncommon and relatively scarce practice. This study provides the first detailed analysis of the Corrections Mental Health Screen (Male) in an Australian setting. Using data for a national sample of 620 male police detainees interviewed as part of the Drug Use Monitoring in Australia (DUMA) program, our objective is to examine the scale’s item-level characteristics in a cross-cultural context, as well as to explore the consequences of a violation of the assumption of unidimensionality. Our results confirm that all 12 items of the CMHS-M are significantly correlated and exhibit strong internal consistency, although several items are relatively uninformative in these Australian data. The item measuring prior experience of psychiatric hospitalisation is particularly uninformative, while items which measure general psychological and antisocial traits (such as the lack of empathy, impulsivity, and interpersonal conflict) are likely to confound measurement in criminal justice settings. A two-dimensional model proves to be a superior fit and has implications for the estimation of the relationship between mental health, crime, and race.